Unauthorized Mining Exploration and Community Welfare In Huamual District, West Seram Regency - Fahrul Fahrul; Muhammad Idul Launuru; Arif Sevfri Diansyah (Publikasi Berkala Pendidikan Ilmu Sosial, 2025)
Unlicensed mining activities (PETI) in Huamual District, Western Seram Regency, Maluku Province, have become one of the primary sources of livelihood for local communities. Mining exploration, despite being a traditional community activity and being government-recognized, enables mining locations to create jobs, thereby increasing income and strengthening socioeconomic welfare. The research method employs a qualitative, phenomenological approach to explore the community's direct experience of the existence of unpermitted mines. The results of the study show that mining without PETI has a positive impact on the community, including reducing the unemployment rate, improving the community's economy, and developing small businesses and empowering local communities. On the other hand, unlicensed mining activities also harm the community and cause environmental damage, including landslides, deforestation, and floods. The community will accept its own risks due to unlicensed mining activities. The community still maintains customary land if there are companies that want to enter. The community lacks the capital of knowledge and does not want any requirements. These findings indicate that people prefer to work in mining areas without permission, aiming to improve community welfare, but are not permitted to manage mining products at the mine site.